The Jeff Mouse Mutant Model for Chronic Otitis Media Manifests Gain-of-Function as Well as Loss-of-Function Effects - Kubinyecz, Oana; Vikhe, Pratik P.; Purnell, Thomas; Brown, Steve D. M.; Tateossian, Hilda (Frontiers in Genetics, 2020)
Chronic otitis media (OM) is the most common cause of hearing loss worldwide, yet the underlying genetics and molecular pathology are poorly understood. The mouse mutant Jeff is a single gene mouse model for OM identified from a deafness screen as part of an ENU mutagenesis program at MRC Harwell. Jeff carries a missense mutation in the Fbxo11 gene. Jeff heterozygotes (Fbxo11Jf/+) develop chronic OM at weaning and have reduced hearing. Homozygotes (Fbxo11Jf/Jf) display perinatal lethality due to developmental epithelial abnormalities. In order to investigate the role of FBXO11 and the type of mutation responsible for the phenotype of the Jeff mice, a knock-out mouse model was created and compared to Jeff. Surprisingly, the heterozygote knock-outs (Fbxo11tm2b/+) show a much milder phenotype: they do not display any auditory deficit and only some of them have thickened middle ear epithelial lining with no fluid in the ear. In addition, the knock-out homozygote embryos (Fbxo11tm2b/tm2b), as well as the compound heterozygotes (Fbxo11tm2b/Jf) show only mild abnormalities compared to Jeff homozygotes (Fbxo11Jf/Jf). Interestingly, three days after intranasal inoculation of the Fbxo11tm2b/+ mice with non-typeable Haemophilus influenzae (NTHi) a proportion of them have inflamed middle ear mucosa and fluid accumulation in the ear suggesting that the Fbxo11 knock-out mice are predisposed to NTHi induced middle ear inflammation. In conclusion, the finding that the phenotype of the Jeff mutant is much more severe than the knock-out indicates that the mutation in Jeff manifests gain-of-function as well as loss-of-function effects at both embryonic and adult stages.